Chemokines, molecular drivers of thromboinflammation and immunothrombosis - Leberzammer, Julian; von Hundelshausen, Philipp (Frontiers in Immunology, 2023)
Blood clotting is a finely regulated process that is essential for hemostasis. However, when dysregulated or spontaneous, it promotes thrombotic disorders. The fact that these are triggered, accompanied and amplified by inflammation is reflected in the term thromboinflammation that includes chemokines. The role of chemokines in thrombosis is therefore illuminated from a cellular perspective, where endothelial cells, platelets, red blood cells, and leukocytes may be both the source and target of chemokines. Chemokine-dependent prothrombotic processes may thereby occur independently of chemokine receptors or be mediated by chemokine receptors, although the binding and activation of classical G protein-coupled receptors and their signaling pathways differ from those of atypical chemokine receptors, which do not function via cell activation and recruitment. Regardless of binding to their receptors, chemokines can induce thrombosis by forming platelet-activating immune complexes with heparin or other polyanions that are pathognomonic for HIT and VITT. In addition, chemokines can bind to NETs and alter their structure. They also change the electrical charge of the cell surface of platelets and interact with coagulation factors, thereby modulating the balance of fibrinolysis and coagulation. Moreover, CXCL12 activates CXCR4 on platelets independently of classical migratory chemokine activity and causes aggregation and thrombosis via the PI3Kβ and Btk signaling pathways. In contrast, typical chemokine-chemokine receptor interactions are involved in the processes that contribute to the adhesiveness of the endothelium in the initial phase of venous thrombosis, where neutrophils and monocytes subsequently accumulate in massive numbers. Later, the reorganization and resolution of a thrombus require coordinated cell migration and invasion of the thrombus, and, as such, indeed, chemokines recruit leukocytes to existing thrombi. Therefore, chemokines contribute in many independent ways to thrombosis.